2020
DOI: 10.2174/1871520620666200516145830
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-372-3p Predicts Response of TACE Patients Treated with Doxorubicin and Enhances Chemosensitivity in Hepatocellular Carcinoma

Abstract: Background: Identification of factors to detect and improve chemotherapy‐response in cancer is a main concern. microRNA-372-3p (miR-372-3p) has been demonstrated to play a crucial role in cellular proliferation, apoptosis and metastasis of various cancers including Hepatocellular Carcinoma (HCC). However, its contribution towards Doxorubicin (Dox) chemosensitivity in HCC has never been studied. Objective: This study aims to investigate the potential role of miR-372-3p in enhancing Dox effects on HCC cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…miRNAs are small, noncoding RNAs that act as crucial posttranscriptional regulators of gene expression by binding to the UTRs of large target mRNAs [27,28]. As an essential member of the miRNA family, miR-372-3p has drawn our attention; it is a highly conserved miRNA among humans and animals [29,30]. However, the specific role of miR-372-3p in DCM has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small, noncoding RNAs that act as crucial posttranscriptional regulators of gene expression by binding to the UTRs of large target mRNAs [27,28]. As an essential member of the miRNA family, miR-372-3p has drawn our attention; it is a highly conserved miRNA among humans and animals [29,30]. However, the specific role of miR-372-3p in DCM has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Co-transfection of miR-372-3p (mimics/inhibitors) and twist1 (mimics/inhibitors) demonstrated that twist1 could partially reverse the effects of miR-372-3p (mimics/inhibitors) on trophoblast cells, which suggested that miR-372-3p may suppress trophoblast migration, invasion and EMT (E-cadherin, N-cadherin, vimentin and twist1) by targeting twist1. Previous studies have reported that miR-372-3p serves important roles in numerous types of disease, for example colorectal cancer, lung squamous cell carcinoma, osteosarcoma, hepatocellular carcinoma (8,(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the relatively novel lncRNAs, microRNAs (miRNAs) remain a focus of research on nucleic acid biomarkers [ 74 ]. miRNA-372-3p, which acts as a tumor suppressor in HCC, has been demonstrated to play a crucial role in cellular proliferation, apoptosis, and metastasis of various cancers, including HCC, colon cancer, and osteosarcoma [ 75 , 76 , 77 ]. Consistent with this, ectopic expression of miR-372-3p reduces cell proliferation and migration and significantly induces apoptosis in HepG2 cells in association with a decrease in the antiapoptotic protein Mcl-1 [ 75 ].…”
Section: Genes Associated With Doxorubicin Resistancementioning
confidence: 99%
“…miRNA-372-3p, which acts as a tumor suppressor in HCC, has been demonstrated to play a crucial role in cellular proliferation, apoptosis, and metastasis of various cancers, including HCC, colon cancer, and osteosarcoma [ 75 , 76 , 77 ]. Consistent with this, ectopic expression of miR-372-3p reduces cell proliferation and migration and significantly induces apoptosis in HepG2 cells in association with a decrease in the antiapoptotic protein Mcl-1 [ 75 ]. Notably, levels of miR-372-3p in the blood of HCC patients responsive to TACE with doxorubicin are significantly higher than those in nonresponders.…”
Section: Genes Associated With Doxorubicin Resistancementioning
confidence: 99%